Alternativas penais e democracia: a democratização da justiça criminal pela política de penas e medidas alternativas: um estudo de caso no Tribunal de Justiça do Estado do Pará, 2008-2010 - MEDEIROS, Josineide Gadelha Pamplona (Universidade Federal do Pará, 2017)
This dissertation brings forward the results of a social and legal investigation on the democratization process of Criminal Justice, as applied amidst the punishment policies and alternative sanctions in the area of criminal execution. Starting out with the assumption that democratization denotes a process of widening opportunities for participation by the citizenry in public affairs, it is understood that such a phenomenon takes place in Brazilian Judiciary as a function of on-going transformation in the role of Justice which is on course to becoming a public space where citizens tend to ever more dramatize social and inter-subjective relationships through the language of law, especially in the realm of fundamental rights. As though that was not enough, the judiciary community is also aware nowadays, in some segments, of certain frameworks in which citizens alien to the legal field have started to partake in the process of judicial interpretation and decision-making, thus extending the circle of players enabled to speak on the law, whereas such an initiative was formerly monopolized by professional jurists, mainly magistrates and by the courts. One such venue seems to be the execution of punishment alternatives in Brazil, and this is so because the National Policy on Punishment and Alternative Measures, inspired by the Tokyo Standards, has fostered the adoption, within the Judiciary, of equipment and public services for execution of punishment and alternative measures which imply, on one hand, the spreading through the legal field of concerns of political and social nature with fundamental rights of the enforcers and, on the other hand, the opening of punishment execution to participation by professionals of nonlegal areas and by community cells involving definition, overseeing and monitoring of punishment alternatives, including the availability of wider opportunities for enforcers to express their opinions and formulations on crimes, penalties and such measures. Within the dissertation reach, such a democratization framework is investigated as from the experience of the Court for Punishment Execution and Alternative Measures with jurisdiction over the Metropolitan Area of Belém, before which an empirical survey was carried out with the purpose of grasping, mainly, the standpoint of Agents of the Judiciary, notably of those working with execution of punishment and alternative measures, to the extent that the legal, social and political burden of performing within the arena of punishment alternatives goes, under a perspective leaning towards democratization in the judicial field.